2022
DOI: 10.1155/2022/6225758
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Molecular Mechanisms of Aloe barbadmsis Miller on Diphenoxylate-Induced Constipation in Mice

Abstract: Aloe barbadensis Miller (Aloe) known as a common succulent perennial herb had been traditionally used in constipation for more than 1,000 years. Aloe contained anthraquinones and other active compounds which had laxative effect and could modulate constipation. However, the therapeutic effects and mechanisms of aloe in constipation were still unclear. To explore the therapeutic effects and mechanisms of aloe in treating constipation, we employed network pharmacology, molecular docking, and mice experiments in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The antidiarrheal activity of the chemical components of Aloe spp. includes polysaccharides, glycoproteins, and anthraquinones, exhibits anti-inflammatory effects [ 122 ], modulates intestinal motility [ 123 ], possesses antimicrobial activity [ 124 ], protects the intestinal mucosa [ 125 ], and regulates ion transport [ 126 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antidiarrheal activity of the chemical components of Aloe spp. includes polysaccharides, glycoproteins, and anthraquinones, exhibits anti-inflammatory effects [ 122 ], modulates intestinal motility [ 123 ], possesses antimicrobial activity [ 124 ], protects the intestinal mucosa [ 125 ], and regulates ion transport [ 126 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the intervention resulted in increased SP and decreased VIP content in mice serum, promoting the contraction of intestinal smooth muscle and enhancing intestinal propulsion. 34 Beck et al conducted a study that demonstrated the inhibitory effect of nitric oxide (NO) on gastrointestinal motility by reducing intracellular calcium levels and relaxing smooth muscle cells through stimulation of intracellular soluble guanylyl cyclase (sGC). 35 Meanwhile, Izzo et al showed that Aloe barbadensis Mill.…”
Section: Potential Mechanisms Of Aloe Barbadensis ...mentioning
confidence: 99%
“…The clear gel inside the leaf is extracted and used as an excellent treatment for various skin wounds and burns, and other skin problems, as it helps speeds up the healing rate, reduces the risk of infection, and improves the quality of skin texture (Hekmatpou et al, 2019). It can also be used as a treatment for chronic constipation, low appetite, and recurring digestive problems (Tang et al, 2022). Vitamins, enzymes, minerals, carbohydrates, lignin, saponins, salicylic acids, and amino acids are among 75 potentially active constituents in Aloe vera (Atherton, 1998).…”
Section: Introductionmentioning
confidence: 99%